2021
DOI: 10.1111/jzo.12939
|View full text |Cite
|
Sign up to set email alerts
|

Grasslands half‐full: investigating drivers of spatial heterogeneity in ungulate occurrence in Indian Terai

Abstract: Grassland ecosystems have declined in their extent globally, driving declines in wild ungulate populations. Even within the remnant grasslands, ungulate distribution is highly heterogeneous for reasons that are not well understood. This in turn undermines both local and landscape level conservation efforts for these often‐neglected ecosystems and the herbivores they support. We investigated grassland‐ungulate relationships in the Terai region of North India, where wild ungulates are patchily distributed across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Besides multiple ecosystem services, grasslands support immense biodiversity and endemism, reflecting their ancient Indian roots. Endemic species like the critically endangered Great Indian Bustard ( Ardeotis nigriceps ), Swamp Grass Babbler ( Prinia cinerascens ), the vulnerable One‐horned rhinoceros ( Rhinoceros unicornis ), and the Swamp deer ( Rucervus duvaucelii ), as well as reptiles like Ophisops lizards, indicate the antiquity of the Indian grassland biomes (Dutta et al 2010; Agarwal & Ramakrishnan 2017; Rastogi et al 2022). Grasslands support the livelihoods and food security of millions of people through agriculture, collection of grass for various purposes, cattle grazing, and sustenance of pastoralism throughout the nation.…”
Section: India's Grasslandsmentioning
confidence: 99%
“…Besides multiple ecosystem services, grasslands support immense biodiversity and endemism, reflecting their ancient Indian roots. Endemic species like the critically endangered Great Indian Bustard ( Ardeotis nigriceps ), Swamp Grass Babbler ( Prinia cinerascens ), the vulnerable One‐horned rhinoceros ( Rhinoceros unicornis ), and the Swamp deer ( Rucervus duvaucelii ), as well as reptiles like Ophisops lizards, indicate the antiquity of the Indian grassland biomes (Dutta et al 2010; Agarwal & Ramakrishnan 2017; Rastogi et al 2022). Grasslands support the livelihoods and food security of millions of people through agriculture, collection of grass for various purposes, cattle grazing, and sustenance of pastoralism throughout the nation.…”
Section: India's Grasslandsmentioning
confidence: 99%
“…The exceptions were grasslands where both short and tall grasses were found, including some areas with extensive livestock grazing. A likely explanation for low herbivore densities in tall grasslands is that palatable grasses for wild ungulates sharply declines within about three months of prescribed winter burning both in PAs and MUFs (Rastogi et al, 2022). We did not find a statistically significant relationship between tiger densities and proximity to edges, with tiger density hotspots both occurring forest edges and within the forest-interior (Appendix S6).…”
Section: Discussionmentioning
confidence: 74%
“…Swamp Deer are indicator species of the alluvial floodplains (Ahmed 2007;Singh & Prasad 2013). Many wetlands/swamps in the study area are threatened due (Rastogi et al 2022). The results from the study revealed that about 30% of the overall grasslands were used by the species, with an occurrence probability of more than 40%.…”
Section: Discussionmentioning
confidence: 90%